Aerosol isotopic ammonium signatures over the remote Atlantic Ocean. (May 2016) - Lin, C.T.; Jickells, T.D.; Baker, A.R.; Marca, A.; Johnson, M.T.
Abstract: We report aerosol ammonium 15 N signatures for samples collected from research cruises on the South Atlantic and Caribbean using a new high sensitivity method. We confirm a pattern of isotopic signals from generally light (δ 15 N −5 to −10‰), for aerosols with very low (<2 nmol m −3 ) ammonium concentrations from the remote high latitude ocean, to generally heavier values (δ 15 N +5 to +10‰), for aerosols collected in temperate and tropical latitudes and with higher ammonium concentrations (>2 nmol m −3 ). We discuss whether this reflects a mixing of aerosols from two end-members (polluted continental and remote marine emissions), or isotopic fractionation during aerosol transport. Highlights: Aerosol NH4 δ 15 N measurements with improved sensitivity are reported, confirming a global isotopic distribution pattern. Pattern of isotopic signals may be either mixing between two end members or fractionation during aerosol transport.